Learning Organization as a Factor in Preparing Teachers for Change (Journal of Educational Sciences, 2021)
In today’s rapidly changing world, the content of education, expected results and learning tech- nologies are being constantly improved. In accordance with this process, there is a need of teachers for change. The Article examines the essence of a learning organization as a factor for preparation of teachers of changes. The update content and the new results requires teachers to be ready to implement new ap- proaches in pedagogical activity. Teachers need to constantly learn, improve teamwork, learn from each other, develop critical thinking skills, over-subject skills. The creation of a self-learning organization in the structure of the teachers of the place of work require certain organizational measures in management activities. The methodological foundations of research are systemic, activity and research approaches, methods of analysis of scientific and theoretical literature, methods of experiments, generalization and comparison of experimental results were used, experience was used, so the recommendations for the development of teachers’ readiness for changing. The theoretical foundations, approaches and principles of a self-learning organization have been determined, a model for preparing the teachers for changes, content, structure and teaching methods have been developed, criteria and indicators of teachers’ readi- ness to change have been determined. Of practical importance is the development of a methodology for preparing teachers for changes through self-learning organizations.In conclusion, the effectiveness of self-learning organizations in preparing the teachers for changes is noted.Key words: learning organization, changes, updated educational content, teacher communities.